CapsoCam SV-1 Versus PillCam SB 3 in the Detection of Obscure Gastrointestinal Bleeding: Results of a Prospective Randomized Comparative Multicenter Study. Issue 3 (March 2019) - Zwinger, Lilli L.; Siegmund, Britta; Stroux, Andrea; Adler, Andreas; Veltzke-Schlieker, Winfried; Wentrup, Robert; Jürgensen, Christian; Wiedenmann, Bertram; Wiedbrauck, Felix; Hollerbach, Stephan; Liceni, Thomas; Bojarski, Christian
Abstract : Background and Study Aim: Newer capsule with a panoramic viewing mode is available and might increase the detection rate of bleeding lesions in patients with obscure gastrointestinal bleeding (OGIB). Furthermore, an improved patient acceptance rate is expected. Materials and Methods: In a randomized prospective comparative multicenter study, patients with OGIB were included and examined either with CapsoCam SV-1 or with PillCam SB 3. Detection of bleeding lesions, transit, and evaluation time and adverse events were evaluated. Physicians were interviewed about their experience with both capsules and the evaluation software. A detailed subject questionnaire analyzed acceptance of each capsule. Follow-up was 3 months. Results: In total, 181 patients with OGIB were recruited into the study. After exclusion of 28 patients 153 patients were randomized and CapsoCam SV-1 (n=78) or PillCam SB 3 (n=75) was administered. CapsoCam SV-1 detected more cases of bleeding (31/79, diagnostic yield 39.7%) compared with PillCam SB 3 (26/75, diagnostic yield 34.6%, NS). Transit time of both capsules was not different. Evaluation time with PillCam SB 3 was superior to CapsoCam SV-1 (27 vs. 40 min, P =0.01). In total, 95% of the physicians were satisfied with each capsule system and evaluation software. The acceptance rate of the patients to retrieve the CapsoCam SV-1 was high. Adverse events/serious adverse events were 17.9%/1.3% with CapsoCam SV-1 and 16%/0% with PillCam SB 3. Rebleeding rate was 28.75% within 3 months. Conclusions: CapsoCam SV-1 detected more lesions; however, relevant bleeding sources were visualized by both capsules. Physician's satisfaction was high with both capsule systems and evaluation software. Patient's acceptance with CapsoCam SV-1 was unexpectedly high. Serious adverse events were 0% with PillCam SB 3 and 1.3% with CapsoCam SV-1.